Signs and Demonstrations from Aristotle to Radulphus Brito - Marmo, Costantino, author.
1 online resource (512 pages)
Keywords: In the Posterior Analytics Aristotle contrasts demonstrations with syllogisms through signs. In the Prior Analytics he defines a sign as a demonstrative premise. One is thus led to ask: is a sign a demonstration? This book reconstructs the history of the notion of “demonstration through signs” from roughly the third through to the thirteenth century. It examines the work of Aristotle’s Greek, Arabic, and Latin commentators, both within and outside the tradition of the Posterior Analytics .